Directed Financial Networks using Granger Causality: A Study on Stock Markets of Pakistan and its Major Trading Partners - Ayesha Latif; Nadir Khan; Safiullah (iRASD Journal of Management)
This study is conducted with the aim to construct and analyze directed financial networks of Pakistan and its major trading partners. Five major export partners of Pakistan are USA, China, UK, Germany and UAE. While major import partners are USA, China, Indonesia., Saudi Arabia and UAE. Granger causality test was conducted using the stock returns from each stock exchange. The test was used to detect whether a change in the prices one stock exchange cause a change the prices of others. The results reveal that none of the exporting or importing country’s stock exchange cause any change in the Pakistan stock exchange neither does PSX cause any change in other stock exchanges. However, some countries like Shanghai and New York, Shanghai and Frankfurt show a unidirectional causality.